Adapting Fuzzy Linguistic SERVQUAL Model: A comparative analysis of bank services in Malaysia - Vincent, Charles; Kumar, Mukesh; Suggu, Srinivas (CENTRUM Publishing, 2012)
Fuzzy logic provides a useful tool for dealing with decisions in which the phenomena are imprecise and vague. The application of non-parametric statistical analysis in the SERVQUAL model could be more meaningful in the presence of skewed distribution of customers’ scores. The current paper aims to construct a fuzzy SERVQUAL method for evaluating the service quality of banks in Malaysia for different market segments, namely conventional, Islamic and foreign banks. Further, a comparison of service quality gaps has been assessed with respect to demographic characteristics of the customers to answer a fundamental question “What do customers want from banking services and which elements of service quality is important for different customers?” The sample is made up of 766 bank customers, consisting of the customers from conventional, Islamic and foreign banks from different parts of Malaysia. The data have been collected by using the structured questionnaire, which consists of three sections. Section 1 deals with consumers’ usage of banking channels and their banking behavior. Section 2 contains 26 statements related to service quality dimensions based on past literature. Finally, Section 3 contains the questions related to the socio-demographic profiles of respondents. First, the effectiveness of the Fuzzy linguistic scale and the Likert scale was compared by using the test of internal consistencies on dimensions of service quality. Further, the assumptions of analysis of variance (ANOVA) were checked for appropriateness of statistical analysis to be performed for the comparative analysis. Finally, the SERVQUAL gaps are analyzed and compared across 3 market segments and different groups of customers based on demographic characteristics by using non-parametric approach.
Keywords: Fuzzy linguistic scale; SERVQUAL; Malaysian banks; http://purl.org/pe-repo/ocde/ford#5.02.04